2017
DOI: 10.1177/1550059417717398
|View full text |Cite
|
Sign up to set email alerts
|

High-Intensity Chronic Stroke Motor Imagery Neurofeedback Training at Home: Three Case Reports

Abstract: Motor imagery (MI) with neurofeedback has been suggested as promising for motor recovery after stroke. Evidence suggests that regular training facilitates compensatory plasticity, but frequent training is difficult to integrate into everyday life. Using a wireless electroencephalogram (EEG) system, we implemented a frequent and efficient neurofeedback training at the patients' home. Aiming to overcome maladaptive changes in cortical lateralization patterns we presented a visual feedback, representing the degre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 36 publications
0
32
1
Order By: Relevance
“…Since it was shown that repeated use of neuroelectric or neuromagnetic BCI systems after stroke can lead to long‐lasting effects on functional brain oscillatory activity (e.g., magnitude of event‐related desynchronization70 or hemispheric blood‐oxygen‐level‐dependent signals, BOLD39), follow‐up studies indicated that such BCI paradigm may also lead to structural reorganization of the brain (as measured by diffusion tensor imaging71, 72, 73, 74). Another study that used real‐time functional magnetic resonance imaging showed that just two training sessions were sufficient to increase ipsilesional cortico‐subcortical resting state connectivity in 3 out of 4 stroke survivors 75…”
Section: Discussionmentioning
confidence: 99%
“…Since it was shown that repeated use of neuroelectric or neuromagnetic BCI systems after stroke can lead to long‐lasting effects on functional brain oscillatory activity (e.g., magnitude of event‐related desynchronization70 or hemispheric blood‐oxygen‐level‐dependent signals, BOLD39), follow‐up studies indicated that such BCI paradigm may also lead to structural reorganization of the brain (as measured by diffusion tensor imaging71, 72, 73, 74). Another study that used real‐time functional magnetic resonance imaging showed that just two training sessions were sufficient to increase ipsilesional cortico‐subcortical resting state connectivity in 3 out of 4 stroke survivors 75…”
Section: Discussionmentioning
confidence: 99%
“…The pilot study involved four chronic patients with various degrees of motor impairment and stroke characteristics. In recent years, few studies have explored the potential of real-time NF for improving motor performances in stroke using different imaging modality such as fMRI (Liew et al, 2016), EEG (Pichiorri et al, 2015;Zich et al, 2017) or functional Near-Infrared Spectroscopy -NIRS (Mihara et al, 2013). A recent systematic review on fMRI NF for motor training in healthy subjects and stroke patients (Wang et al, 2017) indicated that real-time fMRI is effective in promoting self-regulation of targeted areas and has potential to improve motor outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The latter furnished a proof-of-concept for a mobile, low-density EEG system for effective NFB training at the home of the participant. Furthermore, recent case study reports by [39] strengthened the notion that MI training at home can lead to noticeable changes in brain patterns. Considering the AAD paradigm there is no reference study or standardized training protocol to date.…”
Section: Introductionmentioning
confidence: 86%